Respuesta :

Answer/Step-by-step explanation:

Since ∆PHS ≅ ∆CNF, therefore:

<P ≅ <C,

<H ≅ <N

<S ≅ <F

Thus:

Since, <P ≅ <C, therefore,

36° = (4z - 32)°

36 = 4z - 32

Add 32 to both sides

36 + 32 = 4z

68 = 4z

Divide both sides by 4

68/4 = z

17 = z

z = 17

Since <H ≅ <N, therefore:

6x - 29 = 115°

Add 29 to both sides

6x = 115 + 29

6x = 144

Divide both sides by 6

x = 114/6

x = 24

m<F + m<C + m<N = 180° (sum of ∆)

(3y - 1) + (4z - 32) + 115 = 180 (substitution)

Plug in the value of z and solve for y

3y - 1 + 4(17) - 32 + 115 = 180

3y - 1 + 68 - 32 + 115 = 180

3y + 150 = 180

Subtract 150 from both sides

3y = 180 - 150

3y = 30

y = 10

The value of x, y and z are 24, 10 and 17 respectively.

PHS≅CNF

Therefore,

∠P ≅ ∠C

∠H ≅ ∠N

∠S ≅ ∠F

36 = 4z - 32

36 + 32 = 4z

4z = 68

z = 68 / 4

z = 17

6x - 29 = 115

6x = 115 + 29

x = 144 / 6

x = 24

3y - 1 = 180 - 115 - (4z - 32)

3y - 1 = 180 - 115 - 4z + 32

3y - 1 = 97 - 4(17)

3y - 1 = 29

3y = 30

y = 30 / 3

y = 10

learn more: https://brainly.com/question/20502277?referrer=searchResults